The Influence and Legacy of Old Shanghai Music - Yuan , Yao; Chareawrum, Khemarin (Journal of Roi Kaensarn Academi, 2024)
Old Shanghai music, a defining element of 20th-century Chinese culture, has significantly influenced the evolution of modern Chinese pop music while preserving vital cultural memories. Its legacy is reflected in contemporary musicians' adaptation of its stylistic elements, its representation of Shanghai’s socio-historical transformation, and its role in fostering international cultural exchange across Southeast Asia, Japan, and beyond. Following China's reform era, Old Shanghai music has gained renewed attention as a key component of nostalgic culture and urban heritage. This study examines the extensive literature on Old Shanghai music, including seminal works like The History of Modern Chinese Music and Yellow Music, alongside scholarly articles that explore its cultural hybridity, societal implications, and historical significance. By analyzing these contributions, this research underscores Shanghai’s pivotal role in modernizing and globalizing Chinese music, highlighting the enduring fusion of Eastern and Western styles and their profound impact on the development of contemporary Chinese popular music and culture.